2006
DOI: 10.1007/s00436-005-0121-8
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and physico-chemical characteristics of recombinant cMDH and mMDH of Clonorchis sinensis

Abstract: The cytosol and mitochondrial malate dehydrogenases (MDHs, EC 1.1.1.37) of Clonorchis sinensis were expressed in Escherichia coli as a fusion protein with a 6xHis and GST tag, respectively. The cytosol MDH of Clonorchis sinensis (Cs-cMDH) has higher resistibility to acid than mitochondrial MDH (Cs-mMDH). The Cs-cMDH also has higher heat resistibility and thermal stability than Cs-mMDH. Although there is only 22.8% identity between the amino acid sequences of Cs-cMDH and Cs-mMDH, they share several conserved re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…In recent years, our laboratory has constructed a fulllength cDNA plasmid library from C. sinensis adult and established an expression profile comprising 1,775 unigenes (Xu et al 2004), many of which were first cloned and characterized, and most of them were evaluated of their potential for diagnosis Ma et al 2007;Wu et al 2007), vaccine (Huang et al 2007;Zhou et al 2008), and drug target (Zheng et al 2006). Identifying the molecules involve in the development of the parasite and of its pathogenesis is also our important goal.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our laboratory has constructed a fulllength cDNA plasmid library from C. sinensis adult and established an expression profile comprising 1,775 unigenes (Xu et al 2004), many of which were first cloned and characterized, and most of them were evaluated of their potential for diagnosis Ma et al 2007;Wu et al 2007), vaccine (Huang et al 2007;Zhou et al 2008), and drug target (Zheng et al 2006). Identifying the molecules involve in the development of the parasite and of its pathogenesis is also our important goal.…”
Section: Introductionmentioning
confidence: 99%
“…mMDH is a key enzyme in the tricarboxylic acid cycle and in the malate-aspartate shuttle. Zheng et al [78][79][80] have demonstrated that glycolytic enzymes are essential required for the survival and pathogenesis of C. sinensis [78][79][80].…”
Section: Enzymes Of Energy Metabolismmentioning
confidence: 99%
“…Fumarase (EC 4.2.1.2) from A. suum has been recombinantly expressed and purified in good yield, but no inhibitors of this enzyme have been reported [196]. Similarly, recombinant mitochondrial malate dehydrogenase from C. sinensis has been produced and partially characterised [197,198]. 4,4'-Bisdimethylaminodiphenylcarbinol (Michler's hydrol; Scheme 5) inhibits the mitochondrial enzyme from this species but not the cytoplasmic isoform [198].…”
mentioning
confidence: 99%
“…Similarly, recombinant mitochondrial malate dehydrogenase from C. sinensis has been produced and partially characterised [197,198]. 4,4'-Bisdimethylaminodiphenylcarbinol (Michler's hydrol; Scheme 5) inhibits the mitochondrial enzyme from this species but not the cytoplasmic isoform [198]. The mechanism of this inhibition has not been determined.…”
mentioning
confidence: 99%